Hypoglycemic effects of dendrobium officinale leaves - Lv, Ming; Liang, Qingqing; He, Xiaofang; Du, Xiaocui; Liu, Yuhan; Liu, Yan; Fang, Chongye (Frontiers in Pharmacology, 2023)
Introduction: Numerous studies have demonstrated that the stems of D. officinale have the effect of lowering blood glucose, but the leaves of D. officinale have seldom been investigated. In this study, we mainly studied the hypoglycemic effect and mechanism of D. officinale leaves. Methods: Initially in vivo, male C57BL/6 mice were administered either standard feed (10 kcal% fat) or high-fat feed (60 kcal% fat) along with either normal drinking water or drinking water containing 5 g/L water extract of D. officinale leaves (EDL) for 16 weeks, and changes in body weight, food intake, blood glucose, etc., were monitored weekly. Next in vitro, C2C12 myofiber precursor cells which were induced to differentiate into myofibroblasts and cultured with EDL to detect the expression of insulin signaling pathway related proteins. HEPA cells were also cultured with EDL to detect the expression of hepatic gluconeogenesis or hepatic glycogen synthesis related proteins. Eventually after separating the components from EDL by ethanol and 3 kDa ultrafiltration centrifuge tube, we conducted animal experiments using the ethanol-soluble fraction of EDL (ESFE), ethanol-insoluble fraction of EDL (EIFE), ESFE with a molecular weight of >3 kDa (>3 kDa ESFE), and ESFE with a molecular weight of <3 kDa (<3 kDa ESFE) for intensive study. Results: The results in vivo revealed that the mice fed the high-fat diet exhibited significantly decreased blood glucose levels and significantly increased glucose tolerance after the EDL treatment, whereas the mice fed the low-fat diet did not. The results in vitro showed that EDL activated the expression of protein kinase B (AKT), the phosphorylation of AKT, and the expression of downstream GSK3β in the insulin signaling pathway. EDL treatment of HEPA cells confirmed that EDL did not affect hepatic gluconeogenesis or hepatic glycogen synthesis. In the experiment of studying the composition of EDL, we found that the >3 kDa ESFE displayed the effect of lowering blood glucose. In summary, the effect of EDL in lowering blood glucose may bethanole achieved by activating the insulin signaling pathway to increase insulin sensitivity, and the main functional substance was contained within the >3 kDa ESFE. Discussion: The findings of this study represent a reference point for further exploration of the hypoglycemic effects of D. officinale leaves and may assist in both the identification of new molecular mechanisms to improve insulin sensitivity and the isolation of monomeric substances that lower blood glucose. Furthermore, the obtained results may provide a theoretical basis for the development of hypoglycemic drugs with D. officinale leaves as the main component.